Outcomes of Salvage Resection and Radiosurgery Following Failed Primary Treatment of Vestibular Schwannomas. (May 2022) - Kay-Rivest, Emily; Golfinos, John G.; McMenomey, Sean O.; Friedmann, David R.; Jethanamest, Daniel; Kondziolka, Douglas; Roland, J. Thomas
Objective: To evaluate outcomes following salvage microsurgery (MS) and salvage stereotactic radiosurgery (SRS) after failure of primary treatment for vestibular schwannomas (VS). Study Design: Retrospective chart review. Setting: Tertiary referral center. Methods: Patients with more than 1 intervention for their VS were divided into 4 groups: MS followed by SRS (n = 61), MS followed by MS (n = 9), SRS followed by MS (n = 7), and SRS followed by SRS (n = 7), and outcomes were evaluated. Results: A total of 77 patients were included (84 procedures). In group 1 (MS then SRS), 3% developed a decline in facial function, 3% developed trigeminal sensory loss, and 13% patients had gradual improvement of facial nerve function following SRS. Group 2 (MS then MS) had the highest rates of facial nerve deterioration, although all but 1 patient achieved a House-Brackmann score of II or III. Gross-total resection (GTR) was achieved in 56% of patients. When a different approach was used for salvage resection, GTR occurred more commonly, and facial nerve outcomes were similar. In group 3 (SRS then MS), GTR occurred in 43% of cases, and 2 of 7 patients developed worsened facial function. In group 4 (SRS then SRS), no patient developed facial weakness after reirradiation, and 1 developed a trigeminal nerve deficit. Conclusions: For MS recurrences/residuals, SRS is the mainstay of treatment and does not preclude facial function recovery. If salvage microsurgery is required, an alternate approach should be considered. For SRS failures, when MS is required, less-than GTR may be preferable, and reirradiation is a potential safe alternative.